Kontrol Optimal Model Matematika Merokok dengan Perokok Berhenti Sementara dan Perokok Berhenti Permanen - Andi Utari Samsir; Syamsuddin Toaha; Kasbawati Kasbawati (Department of Mathematics, Hasanuddin University, 2021)
Abstract This article discusses the optimal control of a mathematical model on smoking. This model consists of six population classes, namely potential to become smoker snuffing class irregular smokers regular smokers temporary quitters and permanent quitters The completion of this research uses the Pontryagin minimum principle and numerically using the forward-backward Sweep method. Numerical simulations of the optimal problem show that with the implementation of education campaigns and anti-nicotine medicine, the smokers can be decreased more quickly and the smoking population who quit permanently can be increased. The implementation of both through large amounts needs to be done from the beginning. The use of control in the form of education campaigns is of great value until the end of the research period means that it needs to be done continuously to reduce the number of smokers in the population.